The application of graphene oxidized combining with decellularized scaffold to repair of sciatic nerve injury in rats - Qiaoling Wang; Jinlong Chen; Qingfei Niu; Xiumei Fu; Xiaohong Sun; Xiaojie Tong (Saudi Pharmaceutical Journal)
This paper combined the decellularized scaffold of sciatic nerve of rats with graphene oxidized (GO), studied and facilitated the regeneration of sciatic nerve of rats, and provided the basis for the clinical application of nanomaterials. GO was prepared through improving Hammer’s Method. Fourier Infrared Spectrum was used to scan and detect the functional groups in GO of sample by using the pellet method, the microcosmic morphological appearance of GO was observed by using the scanning electron microscope. The GO/decellularized scaffold were prepared and operation bridging of injured sciatic nerve was conducted by using the oscillation mixing method. BL-420F Biofunctional Experiment System was used to detect nerve action potential and the maximum tension value of muscles, and the fiber structure of nerve was observed under H-7650 Transmission Electron Microscope (TEM). Scanning electron microscope observed that GO presented a folded and curly single-layer sheet structure. It was soluble in water through ultrasound, brownish, the Fourier Transform Infrared Spectrometer detected the absorption peaks of carbonyl, hydroxy and carboxy, proving that the surface of GO material had many functional groups containing oxygen. Decellularized scaffold combining with GO was applied to repair injury of sciatic nerve, the nerve action potential, maximum tension value of muscle, wet weight value of gastrocnemius, thickness of gastrocnemius, thickness of myelin sheath and diameter of axon of the decellularized scaffold combining with GO group were obviously higher than the decellularized scaffold group and the self-rotating group, approaching to the normal value. All the data were represented by means ± standard deviation (x¯±s) and processed by adopting SPSS 11.0 software. Comparisons among groups were analyzed by variance, and the comparison of two means was detected by student t. The detection level adopted α = 0.05, when P < 0.05, it could be considered that there were significant differences. GO could combine with the biomaterial-decellularized scaffold to repair the injury of sciatic nerve and facilitate the regeneration of injured nerve. This provided new thoughts and theoretical & experimental bases for nanomaterials to be applied to clinic treatment of repair of nerve injury. Keywords: Graphene oxidized, Nanomaterials, Absorption, Decellularized scaffold, Nerve regeneration